2021
DOI: 10.1101/2021.01.11.426207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydroxyapatite pellets as versatile model surfaces for systematic studies on enamel

Abstract: Research into materials for medical application draws inspiration from naturally occurring or synthesized surfaces, just like many other research directions. For medical application of materials, particular attention has to be paid to biocompatibility, osseointegration and bacterial adhesion behavior. To understand their properties and behavior, experimental studies with natural materials such as teeth are strongly required. The results, however, may be highly case-dependent because natural surfaces have the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…It has been suggested that C. albicans does not bind some salivary ligands (e.g., PRPs), when these are in solution, which has been shown for the oral bacterium Streptococcus gordonii [42,45]. It cannot be excluded, however, that the newly yeast cell surface-attached salivary components might mediate the adhesion to the pellicle as well, as has been suggested for saliva-coated S. aureus bacterial cells on saliva-treated titanium [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that C. albicans does not bind some salivary ligands (e.g., PRPs), when these are in solution, which has been shown for the oral bacterium Streptococcus gordonii [42,45]. It cannot be excluded, however, that the newly yeast cell surface-attached salivary components might mediate the adhesion to the pellicle as well, as has been suggested for saliva-coated S. aureus bacterial cells on saliva-treated titanium [31].…”
Section: Discussionmentioning
confidence: 99%
“…The FluidFM combines an atomic force microscope (AFM) cantilever with a microfluidic channel that can be used to immobilize single cells at the free end of the cantilever [25,27,29]. Additionally, AFM-based SCFS allows to quantify the adhesion of microbial cells covered with bodily fluids, like saliva or blood plasma [27,28,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, HAp is an ideal material for dental restorations, as it is the constituent material of the tooth substance [ 19 , 28 ]. It is extremely difficult to develop an artificial HAp enamel for the teeth owing to the difference in roughness.…”
Section: Discussionmentioning
confidence: 99%